Works of Thomas Kyd. - Boas, Frederick S. (Oxford University Press, 1955)
The editor aimed to issue an edition of Thomas Kyd's extant works, as far as they could be identified. He states that 'in the study of pre-Shakespearean literature ... there has been no more marked feature, especially on the Continent, than the increased prominence given to Kyd.'